Zimbabwe : Staff-Monitored Program-Press Release and Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper discusses the Staff-Monitored Program (SMP) for Zimbabwe and highlights that the new government that assumed office following the July 2018 elections is committed to addressing the macroeconomic imbalances, removing structural distortions to facilitate a resumption in growth, and to re-engaging with the international community including by clearing its external arrears. The SMP will be monitored on a quarterly basis and is intended to assist the authorities in building a track record of implementation of a coherent set of economic and social policies that can facilitate a return to macroeconomic stability and assist in reengagement with the international community. With limited access to external financing and the very low level of international reserves, the authorities' room for manoeuvre is very narrow. There are also significant implementation risks of the monetary and exchange rate reforms, as well as addressing governance and corruption weaknesses, which could adversely impact the attainment of SMP objectives.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet